Making of a “dental surgeon” in COVID-19 pandemic; a qualitative study exploring undergraduate dental students perspective - Gulmina Saeed Orakzai , Munazza Gillani , Eruj Shuja , Anum Ashfaq , Rohina Ali ,Sana Iqbal (Journal of Rawalpindi Medical College, 2021)
Background: The closure of educational institutes in Pakistan due to COVID-19 pandemic resulted in a spontaneous shift from traditional to digital teaching and learning. The present study explores the perception of undergraduate dental students regarding its advantages and limitations. Methods: This qualitative study was conducted from December 2020 to February 2021. Utilizing non-probability sampling technique 12 students from three dental colleges of Rawalpindi participated in the study. Three focus group interviews, each with four students were carried out. Data was transcribed verbatim and thematic analysis done. Result: The advantages include becoming a self-directed learner, ease and accessibility. The online teaching was perceived well and participants agreed it saved their time and enhanced time utility. However the challenges included technical issues, behavioral issues and learning compromised clinical skills. Students in their preclinical years were more satisfied with online teaching as compared to those in their clinical years. Conclusion: The present study support the use of online teaching and learning. This mode of teaching allowed the continuation of medical and dental education during these uncertain times. Hence rigorous effects be made to maximize the promising potential benefits of online teaching. Reevaluating the dental curriculum, by incorporating online teaching within traditional dental education will strengthen the curricula and enable future dentist to have an impact in the community. Keywords: COVID-19, Dental education, Dental students, Online teaching, Undergraduate